Project managers soft skills influence in knowledge sharing - Avença, I.; Domingues, L.; Carvalho, H. (Procedia Computer Science, 2023)
Technological evolution allowed a more significant focus on software development projects however, these always showed high failure rates [1] [2]. Project manager role has also gained increasing importance. In the last decade, several studies concluded a positive link between project managers' skills, such as communication, leadership and problem-solving skills, with project success. With the technological evolution and the increasing information availability and knowledge, the knowledge management role in a project environment has become indispensable. However, employees' lack of time or resistance is considered a barrier to knowledge sharing [3]. A survey was developed and delivered to development team members. The results obtained allowed us to conclude that the project manager's leadership positively influences team members' knowledge sharing in information systems. It was also concluded that the project manager's leadership positively influence knowledge sharing through socialization processes and face-to-face conversations, which refers to tacit knowledge sharing.